Crescimento econômico e decomposição da desigualdade de renda do Estado do Piauí - Cavalcanti, Maria Alina Martins Granja (2009)
This dissertation aimed to analyze income inequality amongst the municipalities of the state of Piaui in the period 1995 – 2007 by testing, initially, the validity of the Kuznets’ curve hypothesis and convergence of per capita income. Besides, it was analyzed a decomposition of Theil index based upon the factors: income, gender, race, education and development stage. It was concluded that the necessary and sufficient conditions of convergence are met, as well as the hypothesis of U-inverted of Kuznets’ curve. It is estimated that the state of Piaui would need 27 years to reduce inequality in half between its municipalities, at a speed of convergence of 0.2889. Inequality due to gender declined along the period and education is the variable that most influences the income difference in the state, followed by the factor race. The effect of education on the inequality is significantly enhanced as municipalities are distinguished between those more and less developed.